1997
DOI: 10.1063/1.1148438
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of low temperature radiative cooler for future space missions

Abstract: A probability analysis of space radiator segmenting for increased reliability and reduced mass AIP Conf.Low temperature radiative coolers permit more sensitive, lower temperature detectors for science instruments in space, and can extend the length of missions at low cost and mass. A miniature radiative cooler was designed, constructed, and tested and achieved a stabilized temperature of 34 K with no load and an outer shell temperature of 91 K. This is an improvement upon previous lower limits of radiative coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The coil is assumed to be centered at the PRC with a constant separation distance 5 cm from the edges of the winding to the wall. The thickness of the shielding wall is 5 cm, and the density of the shielding wall is about 160 as reported in [7]. The selection of PRC brings facilitates to the acceleration calculation, since the mass of the PRC is approximately proportional to the radius of the coil.…”
Section: Acceleration Achieved By Magnetic Drivingmentioning
confidence: 97%
See 1 more Smart Citation
“…The coil is assumed to be centered at the PRC with a constant separation distance 5 cm from the edges of the winding to the wall. The thickness of the shielding wall is 5 cm, and the density of the shielding wall is about 160 as reported in [7]. The selection of PRC brings facilitates to the acceleration calculation, since the mass of the PRC is approximately proportional to the radius of the coil.…”
Section: Acceleration Achieved By Magnetic Drivingmentioning
confidence: 97%
“…Solving the (4) gets the current in each turn of the coil as: (5) Multiplying the to both sides of the (5) gets the total Ampereturn of the coil as: (6) It is found that the total Ampere-turn which is responsible for generating local fields is independent to the number of the turn but only a function of the coil radius. The field generated by an Helmholtz coil at the center is (7) Substituting (6) to (7) and imposing the background field, we immediately get the field shielded by a single-stage APSC at the center.…”
Section: Acceleration Achieved By Magnetic Drivingmentioning
confidence: 99%
“…Surprisingly, little theoretical work has been carried out to support the design and development of precision temperature control devices. 1,19,20 Although formulation of accurate, predictive thermal and system models can be difficult, 5,19 and has led to development of various anecdotal criteria for designing thermal control devices, the potential advantages of formulating such models are significant: ͑i͒ existing devices can be tuned to meet specific performance requirements, ͑ii͒ potential designs can be tested theoretically prior to construction, ͑iii͒ methods for improving device performance can be unambiguously determined and implemented, and ͑iv͒ system behavior can be interpreted and modified or controlled as needed.…”
Section: Introductionmentioning
confidence: 99%